Go ahead, Secret Seven - Blyton, Enid; Ross, Tony (Hodder Children's Books, an imprint of Hodder and Stoughton London, 2019)
The Secret Seven are Peter and his sister Janet, Jack, Colin, George, Pam and Barbara. They meet every holiday in the shed at the bottom of Peter and Janet's garden - and solve mysteries, and eat lots of delicious food. But no one can enter the shed without whispering the secret password!